(untitled) (Eurasian Journal of Physics,Chemistry and Mathematics, 2022)
A sun-synchronous orbit, sometimes called an helio-synchronous orbit, is when the Earth orbits the sun at a constant angle relative to the Earth-sun direction. In this work, the analytical technique for third body perturbation on sun-synchronous orbit satellites for different values of Node is considered computed for long period of time At a time interval of 180 day, the dynamic development of sun-synchronous orbits is considered. It was accomplished by utilizing the numerical output results from the celestial mechanics’ version 1 software program package. Numerical motion simulations were performed and The integration was carried out by using the Celestial Mechanics software program SATORB module (Beutler, 2005) created at the University of Bern’s Institute of Astronomy. With input data given by the Two-Line Elements (TLE). Represented by six orbital elements and three Coordinates axes and acceleration components which were used to solve the variation of parameters equations (VOP) using a technique known as collocation method. It is reasonable to assume that the change in orbital elements with the greatest Mean effect on. With the addition of the Geocentric equatorial coordinate system and acceleration combinations. The results show that the third body perturbation has the greatest influence on orbital elements for perigee and Mean anomaly sections and acceleration components with a small influence caused by third body for Geocentric equatorial coordinates sections with increasing and decreasing rate of change as secular and periodic effects and that the perturbation is amplified by satellite heights and mean altitude.